2012
DOI: 10.3945/jn.111.156281
|View full text |Cite
|
Sign up to set email alerts
|

Combined Deficiency of Iron and (n-3) Fatty Acids in Male Rats Disrupts Brain Monoamine Metabolism and Produces Greater Memory Deficits Than Iron Deficiency or (n-3) Fatty Acid Deficiency Alone

Abstract: Deficiencies of iron (Fe) (ID) and (n-3) fatty acids (FA) [(n-3)FAD] may impair brain development and function through shared mechanisms. However, little is known about the potential interactions between these 2 common deficiencies. We studied the effects of ID and (n-3)FAD, alone and in combination, on brain monoamine pathways (by measuring monoamines and related gene expression) and spatial working and reference memory (by Morris water maze testing). Using a 2 × 2 design, male rats were fed an ID, (n-3)FAD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…This is consistent with several previous studies reporting decreased food intake associated with poor growth in rats suffering from ID anaemia [12,28-30]. However, previous depletion studies showed that severe ID decreased relative weight gain (g weight gain per g food intake) [12,28], while in the current study, relative weight gain was the same in rats repleted with Fe and remaining ID. Since neurotransmitters, including DA and 5-HT, are involved in the regulation of food intake [31], it is possible that the reduced food intake of ID rats is related to alterations in monoaminergic neurotransmission.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with several previous studies reporting decreased food intake associated with poor growth in rats suffering from ID anaemia [12,28-30]. However, previous depletion studies showed that severe ID decreased relative weight gain (g weight gain per g food intake) [12,28], while in the current study, relative weight gain was the same in rats repleted with Fe and remaining ID. Since neurotransmitters, including DA and 5-HT, are involved in the regulation of food intake [31], it is possible that the reduced food intake of ID rats is related to alterations in monoaminergic neurotransmission.…”
Section: Discussionsupporting
confidence: 93%
“…We previously showed that the provision of an ID + n-3 FAD diet for 5 weeks post-weaning resulted in an additive 1- to 2-fold increase in DA concentrations in the OB and Str, and decreased 5-HT concentrations relative to controls in the OB at PND 56 [12]. In the current study, at PND 91, rats that remained ID + n-3 FAD had significantly higher DA concentrations than controls (+189%) in the FC.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Omega-3 and omega-6 fatty acids are polyunsaturated fatty acids that maintain membrane fluidity (Simopoulos, 1991); serve as substrates in the biosynthesis of inflammatory eicosanoids (Simopoulos, 2002a; b); modulate dopaminergic neurotransmission (Chalon, 2006; Dervola et al , 2012; Baumgartner et al , 2012), and support other cellular functions. There are three omega-3 fatty acids relevant to human physiology: eicosapentanoic acid (EPA), docosahexanoic acid (DHA), and alpha-linolenic acid (ALA).…”
Section: Dietary Supplementationmentioning
confidence: 99%